Racial Stereotypes Influence Characters’ Responses to The Racism in Dear Martin (2017) by Nic Stone - Linda Amelia; Muhd. Al-Hafizh (English Language and Literature, 2023)
This research is an analysis of the novel by Nic Stone entitled Dear Martin (2017). The purpose of this study was to determine the effect of racial stereotypes on the response of characters in the novel. This study uses racial stereotype theory to analyze the novel. The data are taken from words, phrases, sentences, and quotations in the novel. The method used in this research is descriptive analysis with a qualitative approach to gain a deep understanding, theory development, description of reality and social complexity. The results showed that racial stereotypes on black people have an influence on the response of the characters in them. The results show that characters who believe in certain stereotypes about black people respond to racism as if racism did not happen. Racial stereotypes also influence characters to commit racist acts. On the other hand, characters who do not believe in racial stereotypes think that racist actions are not right and respond to racism as something that should not be tolerated.